1997
DOI: 10.1161/01.cir.96.5.1616
|View full text |Cite
|
Sign up to set email alerts
|

Selective Modulation of Inducible Nitric Oxide Synthase Isozyme in Myocardial Infarction

Abstract: These findings suggest that induction of iNOS activity 72 hours after infarction exerts negative inotropic effects and contributes to the development of myocardial dysfunction; selective modulation of increased iNOS activity by SMT improves cardiac performance, enhances myocardial blood flow, and may be beneficial in the treatment of acute myocardial infarction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
45
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(53 citation statements)
references
References 33 publications
7
45
1
Order By: Relevance
“…Previous reports have shown the expression of iNOS in the unstimulated cardiac tissue. 20,21 Pretreatment with DPCPX prevented the CCPA-induced increase in iNOS expression, suggesting that the selective activation of A 1 ARs indeed triggered the signaling pathway.…”
Section: No and Intracellular Signalingmentioning
confidence: 97%
“…Previous reports have shown the expression of iNOS in the unstimulated cardiac tissue. 20,21 Pretreatment with DPCPX prevented the CCPA-induced increase in iNOS expression, suggesting that the selective activation of A 1 ARs indeed triggered the signaling pathway.…”
Section: No and Intracellular Signalingmentioning
confidence: 97%
“…Furthermore, in the setting of brief ischemia followed by reperfusion, we are interested in whether the reduction in TTC-negative tissue observed in early reperfusion signifies genuine reduction of eventual infarct size following extended reperfusion. Because the stained myocardium consists of a complex mixture of necrotic and surviving myocytes in the early reperfusion, at that time the method of TTC staining has limitations in its accuracy for evaluation of cell necrosis (24); furthermore, inducible NO synthase (iNOS) induced by proinflammatory cytokines occurring during the late phase of postischemic infarction could increase infarct size (47)(48)(49).…”
mentioning
confidence: 99%
“…The beneficial effects were evidenced by decreased infarct size/mortality to some extent; however, NOaspirin appeared to exacerbate cardiac dysfunction: a significantly higher hypertrophy index occurred than in the control group (P Ͻ 0.05). We hypothesized that this is likely NO accumulation during the myocardial infarction due to the excessive supplement of NO released from the NO moiety plus a large amount of NO induced from endogenous iNOS, where a high concentration of NO is believed to be detrimental to cardiac tissue (8,44,48). Interestingly, Liang et al (22) demonstrated that L-arginine (a substrate for NO production) administered at different time points during ischemia-reperfusion exerted different effects on postischemic myocardial injury.…”
mentioning
confidence: 99%
“…4 NO produced by iNOS has been implicated in many pathophysiological states leading to myocardial dysfunction. [5][6][7] Chronic hypoxia modulates NO responses in different cell models, but the relationship between hypoxia and NOS regulation in cardiac tissue is not well understood, 8 and it has not yet been investigated in humans. McQuillan et al 9 found decreased NO production and eNOS expression in endothelial cells exposed to chronic hypoxia.…”
mentioning
confidence: 99%